Radio-absorbent Material Based on Polyvinyl Chloride Filled with Disperse Carbon Fibre. (July 2017) - Vlasenko, E.A.; Bokova, E.S.; Dedov, A.V.; Devin, K.L.
The influence of the content of plasticiser and disperse carbon fibre on the radiophysical characteristics of filled film radio-absorbent materials is investigated.